FITOSOSIOLOGI HUTAN Dl KAWASAN PENYANGGA DANAU SEMAYANG DAN MELINTANG, KALIMANTAN TIMUR - Mustaid Siregar (Research Center for Biology-Indonesian Institute of Sciences, 1997)
This study was aimed at describing the forest types and their degradation at buffer zone of Semayang and Melintang lakes,East Kalimantan.The study was carried out in October 1994 by plot method.Within twenty five main plots, 108 tree species belongs to 75 genera and 38 families were recorded.Ouster analysis shows, the plots have high variation in species.By 50 % similarity index,there could be identified five communities (units)in peat swamp forest,eleven units in riparian forest and two units in kerangas forest.Structure, floristic composition and their degradation of communities at each forests are discussed.